2022
DOI: 10.1371/journal.pone.0264634
|View full text |Cite
|
Sign up to set email alerts
|

Association between metabolic syndrome and 13 types of cancer in Catalonia: A matched case-control study

Abstract: Background Metabolic syndrome (MS) is the simultaneous occurrence of a cluster of predefined cardiovascular risk factors. Although individual MS components are associated with increased risk of cancer, it is still unclear whether the association between MS and cancer differs from the association between individual MS components and cancer. The aim of this matched case-control study was to estimate the association of 13 types of cancer with (1) MS and (2) the diagnosis of 0, 1 or 2 individual MS components. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 47 publications
1
19
0
15
Order By: Relevance
“…listed in Figure 1. Finally, eight observational studies were identified and included in the meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…listed in Figure 1. Finally, eight observational studies were identified and included in the meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
“…These studies were performed in Italy, the Netherlands, Norway, Austria, Sweden, Spain, Korea, and China, and designed as prospective cohorts (23)(24)(25)28), retrospective cohorts (26,27,29), and the matched case-control study (30). Six of them included adult participants in community settings (23,24,(26)(27)(28)30), while the other two included adult patients with vascular diseases (25) and adults with hepatitis B virus infection (29). The sample sizes of the included studies varied between 6,172 and 7,613,865.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations